Settlement History of the Middle Tisza Region in the 4th–6th centuries AD - Zsófia Masek (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae, 2019)
Abstract of PhD thesis submitted in 2018 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Tivadar Vida.